Pengaruh Fasilitas WiFi Di Lingkungan Sekolah Terhadap Motivasi Belajar Siswa - Karimatul Hidayah; Sindi Rosadi; Lisa Rahmawati; Meilisa Sajdah (Journal Innovation In Education, 2024)
WiFi facilities as a learning medium are very helpful for teaching staff and students in the teaching and learning process. It is hoped that the use of WiFi facilities as a learning medium can increase students' learning motivation. The aim of this research is to determine the effect of wifi facilities in the school environment on students' learning motivation at Ibnurusyd Islamic High School, Kotabumi, North Lampung with a sample of 100 students from several levels. Data collection was carried out using the TAM (technology Acceptance Model) method. Data collection techniques can be carried out by distributing questionnaires to students at Ibnurusyd Islamic High School, Kotabumi. The results of the analysis from this research are that the wifi facilities in the learning environment at Ibnurusyd Islamic High School Kotabumi are good for implementing learning activities, this can be seen from the results of the questionnaire which obtained a percentage of 31.3%. The greater the use of WiFi facilities for learning activities as a learning medium, the greater the influence on student learning motivation.